IMPLEMENTATION OF TEACHING AND LEARNING METHODS FOR INFANTS AND TODDLERS IN TASKA: A LITERATURE REVIEW RESPONDING TO CONTEMPORARY PARENTS' EXPECTATIONS - YE HAILU Ye; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study, using a literature review method (kajian perpustakaan), aims to explore the teaching methods used by TASKAs (childcare centers) in Malaysia for infants and toddlers and how they address the educational expectations of contemporary parents. The study summarizes several commonly used teaching methods in TASKAs, including play-based learning, responsive caregiving, sensory learning, individualized learning, and parent-center collaboration. The study found that these methods not only align with the laws of children's physical and mental development but also, in most cases, meet parents' triple educational needs of safety, inspiration, and emotional connection. Finally, the paper recommends that TASKAs continue to enhance the professionalism of their teachers, improve their curriculum, and strengthen collaboration with families and community resources to comprehensively improve the quality of infant and toddler education.